PP.11.12: HYPERTENSION IN LUPUS NEPHRITIS. (June 2015) - Ariba, Y. Ben; Chargui, S.; Maiza, M.; Boussetta, N.; Sayhi, S.; Abid, R.; Ajili, F.; Louzir, B.; Labidi, J.; Othmani, S.
Abstract : Objective: Evaluate hypertension (HT) in a cohort with lupus nephritis (LN) and study its epidemiologic, clinical, histological and therapeutic characteristics. Design and method: The patients included in this study met the criteria fixed by the ARA for the diagnosis of systemic lupus erythematosus. The LN was selected based on the criteria of the International Society of Nephrology (ISN) and the Renal Pathology Society. We reviewed 120 cases of LES hospitalized in the Internal Medicine Department of the Military Hospital of Tunis during 13-year period from 1999 to 2012 and were selected 41 cases of LN. Results: Hypertension was found in 10 patients among the 41 cases studied (25%). There were 2 men and 8 women. The average age of our patients was 34 years. Threatening HT with hypertensive encephalopathy was observed in one patient. HT was associated with diffuse proliferative glomerulonephritis (Class IV) in 6 cases, associated with membranous glomerulopathy (IV + V) in a case. Four patients had clinical and biological signs of thrombotic microangiopathy. In one case, diagnosis of thrombotic microangiopathy was histologically confirmed. The others patients (4 cases) had HT secondary to corticosteroids treatment. The therapeutic strategies consisted of a low salt diet associated with antihypertensive medications in all cases. The angiotensin converting enzyme inhibitors were used in all cases, loop diuretic in 2 cases, beta blockers and calcium channel blockers in 2 others patients. After etiopathogenic treatment, evolution was marked by persistent HT in 4 cases. Conclusions: HT in NL is a poor prognostic factor. It is multifactorial, treatment based on angiotensin converting enzyme inhibitors and its evolution is often favorable.